Chapter Airborne and Ground-Borne Noise and Vibration from Urban Rail Transit Systems - Kouroussis, Georges (InTechOpen, 2017)
This chapter addresses recent progress in the field of polymer thermoelectric materials. It covers a brief introduction to intrinsically conductive polymers and its motivation for thermoelectric utilization. A review about important and recent literature in the field of p-type and n-type polymers for thermoelectric applications is summarized here. For a better understanding of material development issues, doping mechanisms for intrinsically conducting polymers are discussed. Special emphasis is given to n-type polymers, since this group of polymers is often neglected due to unavailability or poor stability during processing. Different possibilities in terms of generator design and fabrication are presented. Recent challenges in this scientific field are discussed in respect to current material development, uncertainty during the measurement of thermoelectric properties as well as temperature stability for the most prominent p-type polymer used for thermoelectric, PEDOT:PSS.